Pop of the Bumpy Mummy : The Notebook of Doom #6 - Cummings, Troy (New York, NY : Branches, Scholastic Inc., 2015)
Alexander's class is going on a sleepover at the Stermont Museum, but something is stealing bright, shiny objects from all over town, including the museum's treasured Ruby Scorpion, and on the night of the visit the young monster hunters finally confront the town's newest monster--a warrior covered entirely by bubble-wrap.
1st-3rd graders.
Grade 2.
Keywords: Monsters -- Juvenile fiction; Elementary schools -- Juvenile fiction; Museums -- Juvenile fiction; Monsters -- Fiction; Elementary schools -- Fiction; Schools -- Fiction; Museums -- Fiction; Horror stories; Horror fiction; Horror fiction